PHYSICAL-CHEMICAL CHARACTERISTICS AND MICROBIOLOGICAL HONEYS OF LA PAMPA (Veterinary Science, 2017)
The honey is defined as the natural sweet substance produced by Apis mellifera bees from the nectar or secretions of plants; or excretions of sucking insects that lives on them.The bees collect, transform and combine with specific substances of their own in the honey comb.The objective of this work was to characterize the honey of the province of La Pampa, based on physico-chemical and microbiological features to search for indicators to ensure better quality for internal and external trade of this product.Thirty-eight samples of different honey-farm, dividing the province of La Pampa in 4 different zones (North, South, East andWest) were analyzed.The physicochemical determinations were pH; total acidity, free acidity and lactone; diastase and ashes. The microbiological analysis made was: determination of total aerobic bacteria count, determination of total coliforms, determination of Salmonella sp and Shigella and the determination of fungi and yeasts.According to the regulations of the CAA results were observed in all cases and regulation MERCOSUR thus also to international standards, concluding honeys in the province of La Pampa can be considered as a good Argentine quality product.
Keywords: Pampeanas honeys; Physico-chemical; Determinations